2021
DOI: 10.1002/syn.22221
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stat3 in NLRP3/caspase‐1‐mediated hippocampal neuronal pyroptosis in epileptic mice

Abstract: Epilepsy, a fairly common neurological disorder, is linked to various sequelae and greatly impairs the quality of life. Meanwhile, there is evidence to suggest an association between pyroptosis and epilepsy. Accordingly, the current study sought to determine the role of signal transduction activator of transcription 3 (Stat3) in pyroptosis in epileptic mice. First, epileptic mouse models were induced by lithium chloride, atropine, and pilocarpine, and HT22 cells were treated with lipopolysaccharide (LPS) to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Hua et al also found that activation of NLRP3 and caspase-1 in neurons can also lead to neuroinflammation [40]. NLRP3 has been found to be significantly elevated in neurons [41] and microglia [42] in the epileptic brain, which is mainly stimulated by intracellular environment and cell membrane receptor signals [43]. Moreover, GPR120 is a membrane receptor that can be internalized into cells to regulate inflammatory factors under disease conditions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Hua et al also found that activation of NLRP3 and caspase-1 in neurons can also lead to neuroinflammation [40]. NLRP3 has been found to be significantly elevated in neurons [41] and microglia [42] in the epileptic brain, which is mainly stimulated by intracellular environment and cell membrane receptor signals [43]. Moreover, GPR120 is a membrane receptor that can be internalized into cells to regulate inflammatory factors under disease conditions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ting-Fa Zhou's research indicated that the JAK2/STAT3 signalling pathway is involved in the protective effect of recombinant human erythropoietin against neuronal alterations and cognitive de cits in experimental endotoxaemia [24] . Furthermore, Qian Jiang's study implicated Stat3-induced activation of NLRP3/Caspase-1-mediated neuronal pyroptosis in epilepsy development in mice [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that the phosphorylated STAT3 (p-STAT3) facilitated histone H3 and H4 acetylation on Nlrp3 promoter, which promoted the expression of NLRP3 ( Liu et al, 2018 ; Jiang et al, 2021b ). STAT3 is one of the major signal transducers of JAKs and plays a role in inducing and maintaining an inflammatory microenvironment ( Zare et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%